2015
DOI: 10.1007/s00421-015-3184-y
|View full text |Cite
|
Sign up to set email alerts
|

Two nights of sleep deprivation with or without energy restriction does not impair the thermal response to cold

Abstract: PurposeIn persons completing exhaustive daily exercise, sleep and energy restriction have been highlighted as risk factors for hypothermia in cold environments. The present study therefore sought to determine the effect of sleep deprivation (SDEP), with and without energy restriction, on the thermal response to cold. MethodsIn a random order, ten recreationally active men (means ± SD: age 25 ± 6 y, body fat 17 ± 5%) completed CAT Tre (P = 0.78). In contrast, perceived thermal discomfort during the initial hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Acute sleep deprivation induced changes in thermoregulation in rats resulting in a decreased peripherical surface temperature due to SA activation during acute stress 115 . However, two nights of sleep deprivation with or without energy restriction did not impair the thermal response to cold in human subjects 116,117 …”
Section: Biological and Clinical Effects Of Distinct Skin Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute sleep deprivation induced changes in thermoregulation in rats resulting in a decreased peripherical surface temperature due to SA activation during acute stress 115 . However, two nights of sleep deprivation with or without energy restriction did not impair the thermal response to cold in human subjects 116,117 …”
Section: Biological and Clinical Effects Of Distinct Skin Stressorsmentioning
confidence: 99%
“… 115 However, two nights of sleep deprivation with or without energy restriction did not impair the thermal response to cold in human subjects. 116 , 117 …”
Section: Biological and Clinical Effects Of Distinct Skin Stressorsmentioning
confidence: 99%
“…Considering the recurrently described influence of sleep deficit on cognition (Killgore, 2010), it might be assumed that the thermoperceptual responsiveness to thermal stimuli would also be affected; however, the results on whole-body thermoperception after a period of sleep loss appear to be inconsistent (Tables 1 and 2). Thus, 53 h of TSD exacerbated thermal discomfort during the initial 1 h of a 4 h exposure to 0 • C air; a response that was independent of any TSD-driven variation in the whole-body thermal state of subjects (Oliver et al, 2015). Such a thermoperceptual sensitization, however, is not supported by other cold-relevant studies (Costa et al, 2010;Esmat et al, 2012;Landis et al, 1998).…”
Section: Sleep Deprivation and Behavioural Thermoeffectorsmentioning
confidence: 79%
“…Contrary to the aforementioned two studies, the others have failed to detect any adverse effects of TSD on thermoregulation to cold, during both resting conditions (Caine-Bish et al, 2004;Costa et al, 2010;Fiorica et al, 1968;Oliver et al, 2015) and moderateintensity exercise (Kolka et al, 1984). Of interest is the work of Oliver et al (2015) and Costa et al (2010), who, by using a within-subject design, found that 53 h of TSD combined with or without negative energy balance neither perturbed thermoeffector capacities (Oliver et al, 2015) nor modulated the immune reactions (the suppression of circulating lymphocytes, neutrophil degranulation and saliva secretory immunoglobulin A) evoked by acute cold (0 • C air) stress (Costa et al, 2010). Lastly, the rewarming response after a period of whole-body cooling does not appear to be disturbed by TSD (Esmat et al, 2012;Oliver et al, 2015).…”
Section: New Findingsmentioning
confidence: 92%
See 1 more Smart Citation